Strategi Periklanan Kosmetik Efektif Untuk Generasi Y Menggunakan Celebrity Endorsement - Afra Nazhirah; Jono Mintarto Munandar; Ujang Sumarwan (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Celebrity endorsement on social media has become a trendy way to advertise today. Examining the effectiveness of celebrity endorsers using the familiarity variable is deemed necessary, considering the risks that arise from selecting inappropriate celebrities. It is also important to explore whether different categories lead to different responses. The aim of the study was to analyze the effect of differences in endorser familiarity and product categories on compatibility with products, attitudes towards advertisements and brands and purchase intentions of Y generation consumers in cosmetic advertisements. This research is a 2x2 factorial experimental study using Multivariate Analysis of Variance (MANOVA). There were 2 stages of the research, the first stage was the pre-test with 30 research participants to select celebrities and the second stage was the main test with 156 participants who were divided into 4 experimental groups. The results of the study stated that differences in celebrity familiarity had no effect on compatibility with products and attitudes towards brands, but had an effect on attitudes towards advertisements and purchase intentions. Differences in product categories and interactions between familiarity and categories show insignificant results. Celebrity endorsers with high or low familiarity currently both have the same potential and each endorser has its own market. Companies should increase consumer product involvement by repeating information. Keywords: attitude towards advertising and brand, endorser familiarity, experimental study, purchase intention, product categories